Gasification of coal water mixture in an entrained-flow gasifier: Effect of air and oxygen mixing ratio. (25th January 2018) - Oh, Gunung; Ra, Ho Won; Yoon, Sung Min; Mun, Tae Young; Seo, Myung Won; Lee, Jae Goo; Yoon, Sang Jun
Highlights: Effect of air and oxygen mixing ratio in an entrained-flow coal gasification is studied. Gasification efficiency was affected by feed flow rate of gasification agent. Equivalence ratio shows a significant effect on gasification than the feed flow rate. Optimal equivalence ratio and air/O2 ratio condition were founded. Abstract: Entrained-flow gasifiers used in commercial integrated gasification combined cycles are usually oxygen-blown. However, oxygen-blown gasification system is expensive to install and operate due to the equipment involved in oxygen purification and supply. To resolve this issue, this study mixed air and oxygen to perform coal gasification. An entrained-flow gasifier of 1 T/D scale was used with the coal water mixture as feedstock. Gasification was carried out at a temperature range of 970–1220 °C, an equivalence ratio of 0.25–0.62, and an air/O2 ratio of 2.17–9.0. With an increasing gasification temperature, the amount of CO in the syngas increased while CO2 and CH4 decreased. Carbon conversion and cold gas efficiency continued to increase with the gasification temperature. In the equivalence ratio test, cold gas efficiency reached 52.1% at around 0.53 before decreasing under a fixed air flow rate of 90 N m 3 /h. By performing gasification with a varying air/O2 ratio after fixing the flow rate, the influence of the equivalence ratio was examined. In addition, the influence of the flow rate was observed through changes in the air/O2 ratio of the gasification agent with fixing the equivalence ratio. The maximum carbon conversion and cold gas efficiency were 90.7 and 57.7%, respectively, and the optimal air/O2 ratio fell in the range of 2.86–3.1.